The Question of God's Perfection : Jewish and Christian Essays on the God of the Bible and Talmud - Hazony, Yoram,; Johnson, Dru, (Philosophy of Religion - World Religions, 2019)
Philosophers have often described theism as the belief in the existence of a "perfect being"-a being that is said to possess all possible perfections, so that it is all-powerful, all-knowing, immutable, perfectly good, perfectly simple, and necessarily existent, among other qualities. But such a theology is difficult to reconcile with the God we find in the Bible and Talmud. The Question of God's Perfection brings together leading scholars from the Jewish and Christian traditions to critically examine the theology of perfect being in light of the Hebrew Bible and classical rabbinic sources. Contributors are James A. Diamond, Lenn E. Goodman, Edward C. Halper, Yoram Hazony, Dru Johnson, Brian Leftow, Berel Dov Lerner, Alan L. Mittleman, Heather C. Ohaneson, Randy Ramal, Eleonore Stump, Alex Sztuden, and Joshua I. Weinstein.